(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
Abstract— Experiment test for premixed laminar combustion of ethanol-air mixtures has been conducted in a tube technique. The laminar burning velocities of premixed homogeneous Ethanol fuel and air mixtures are determined over a wide range of equivalence ratio at elevated temperatures. The experimental apparatus has been modified for apprehension of flame behaviors at 340 K with both ends open to the atmosphere. For each of the flame speeds, unburned gas velocities and flame surface areas have been measured and computed to determine burning velocity. Repeatable and reliable experimental data are obtained in this rig, showing good agreements with previous data. Laminar burning velocities are increased with elevated temperatures.